A Thematic Review on Composition of Board of Directors (BOD) and Its Impact on Performance - Dhungel, Dipti (NCC Journal, 2018)
This thematic paper has been prepared to find out how the composition of Board of Directors makes impact on performance of firms. To find this impact, the articles published in international journals have been reviewed. In addition to this detailed study of the legislator, the provision regarding composition of BOD in Nepal was made as stated in BAFIA and Company Act. The Board of Directorsis the elected members among the shareholders who could best represent the interest of each and every member. Corporate boards are one of the, if not the most important, internal corporate governance mechanisms that monitor and advise management in fulfilling the mandate to protect shareholder interests.There is still much debate as to the relationship between firm performance and boards of directors, which are arguably the main component of corporate governance.The thematic review concludes that the relationship between BOD and performance was not found on the basis of existing literature reviewed. Thus, the study opened the ground for the researcher to test this empirically. NCC Journal Vol. 3, No. 1, 2018, Page: 65-70